Implementation of QR-based treasure hunt game to improve young students’ English vocabulary mastery - Alamanda Mutia Safitri; Trisanti, Novia (Universitas Negeri Semarang, 2025)
This study explores the effectiveness of a QR-based Treasure Hunt game in enhancing English vocabulary mastery among 7th grade students at a public junior high school located in Ungaran, a district in Semarang Regency, Central Java, Indonesia. Despite the growing interest in gamification and mobile-assisted learning, the use of QR codes specifically for vocabulary acquisition in EFL classrooms has received little scholarly attention—underscoring the need for targeted investigation in this area. Using a quasi-experimental design, students were divided into control and experimental groups, with vocabulary mastery assessed through pre-test and post-test evaluations. The control group, which followed traditional teaching methods, showed minimal vocabulary improvement, whereas the experimental group demonstrated significant gains after engaging with the QR-based gamified approach. The interactive nature of QR codes encouraged active participation, allowing students to scan, solve, and engage with challenges in a structured format. The findings confirm that gamified learning fosters engagement, reinforcing Cognitive Load Theory by breaking vocabulary learning into manageable, interactive components. While most students responded positively, observations revealed that some required additional guidance, highlighting the need for structured instructional support when implementing gamification. This study contributes to the field of educational technology, demonstrating the potential of gamification in language acquisition and student motivation. By integrating QR-based activities into EFL instruction, schools can modernize teaching practices, improving both learning outcomes and engagement. Future research should explore long-term retention, learner diversity, and expanded gamification models to further refine technology-enhanced vocabulary instruction.